Impelementasi Pelatihan Pengelolaan Kelas Berbasis Karakter Di MI Darul Ulum Kota Tengah Rokan Hulu - Gusmana, Iin; Magdalena, Rani; Siagian, Mustika Syariah (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2025)
Strengthening teachers' competence in classroom management is a crucial aspect of creating an effective and conducive learning environment, especially at the elementary education level. This community service program aimed to enhance the capacity of teachers at MI Kota Tengah, Rokan Hulu, through character-based classroom management training. The training was designed to integrate classroom management strategies with character education in order to foster moral values within the learning process. The implementation began with a needs assessment conducted through direct observation and in-depth interviews with the principal and teachers, which served as the basis for developing contextually relevant training modules. The training was delivered through an interactive workshop using lectures, group discussions, case studies, and classroom simulations. After the workshop, teachers received classroom-based mentoring and feedback from the service team. Evaluation was carried out using pre-test and post-test instruments, as well as classroom observations and teacher reflections. The results indicated a significant improvement in teachers’ understanding and skills in managing classrooms and incorporating character values into instruction. In conclusion, the training effectively enhanced teachers’ pedagogical competence and contributed to building a more positive and character-oriented learning environment